Analisis Yuridis Penyelesaian Tindak Pidana Kekerasan Seksual dengan Pendekatan Restorative Justice - Asma Indah; Fuad Nur (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to find out how the restorative justice approach is applied in resolving cases of sexual violence based on the legal system in Indonesia and to understand the legal consequences of sexual violence cases resolved through restorative justice. The type of research used in this study is normative legal research. Normative legal research is a research process that refers to the laws and regulations that are in effect and relevant to the legal issues being studied. The approaches used in this research are the statute approach and the conceptual approach.From the results of this research, it can be concluded that in Indonesia, the legal regulations regarding the application of the restorative justice approach are not yet comprehensively and consistently regulated in one complete regulation and are still scattered across several regulations, especially in handling sexual violence crimes. This can potentially cause disharmony and gaps in law enforcement practices. The legal consequence of applying restorative justice in sexual violence cases is that it shifts the focus of law enforcement from punishing the offender to non-retributive resolution, which has the potential to halt the criminal justice process, thus creating legal uncertainty and weakening the preventive function of criminal law.